Thyroglossal Duct Cyst: Clinical Insights from a Case Report - Christeven, Robert; Hartungi, Florean (Nusantara Medical Science Journal, 2025)
Introduction and importance: A thyroglossal duct cyst (TGDC) is the most common congenital mass found in the neck region. TGDC originates from the thyroglossal duct and persists along the descending groove of the thyroid gland, from the foramen caecum to the superior thyroid gland in front of the trachea. Presentation of case: A 46-year-old man presented with a slowly enlarging lump at the anterior midline of the neck, first noticed about 10 years earlier. On examination, a well-defined, round, cystic mass measuring 3.5 × 3.3 cm was found superior to the thyroid cartilage. The mass moved with tongue protrusion and swallowing and was mobile, painless, and non-tender. These findings were consistent with a thyroglossal duct cyst. Discussion: Thyroglossal duct cyst (TGDC) is a congenital midline neck mass resulting from the persistence of the thyroglossal duct during thyroid descent. Diagnosis is based on clinical features and imaging, with the Sistrunk procedure serving as the gold standard treatment to prevent recurrence. The patient underwent successful surgical excision without complications, and histopathology confirmed the diagnosis. Conclusions: The Sistrunk's Procedure surgery was conducted successfully with no postoperative complication in this case.